La juventud de los hijos del rey en la Castilla del siglo xv - Ana Echevarria Arsuaga (Mélanges de la Casa de Velázquez)
The sources of this article are the medieval didactic treatises about the education of the Princes. In these, youth is seen as a stage which is characterised by both physical and moral disorder and chaos. The image of youth is defined as the opposite of old age, and is based on classical sources which at the end of the 14th century had already begun to shape the humanist cultural model. Education was the way to order and direct the actions of these young people towards a worthy adult life. We have focused on the king’s household as the centre for the education of the Castilian social elite, analysing the theoretical bases of its organisation and its practical organisation during the first half of the 15th Century. Finally, the positive assessment which medieval authors ascribe to youth is examined as a positive factor in education in specific attitudes, customs and the acquisition of religious faith.